BEAM25 program for numerical simulation of the processes of high-current electron beam shaping, acceleration and transportation - Gordeev, V.S.; Mikhailov, E.S. (Вопросы атомной науки и техники, 2001)
The paper presents the description of a self-consistent difference scheme and numerical algorithm of a joint solution of Maxwell equations and equation of charged particle motion on a regular non-uniform mesh. The given algorithm is applied to calculate non-stationary electromagnetic processes in axially symmetric structures consisting of components with different electric and magnetic properties as well as to simulate numerically the processes of high-current electron beam shaping, acceleration and transportation. The example of the program use for the calculation of electron beam characteristics in a STRAUS-2 accelerator diode is given. The obtained coincidence of calculation and experimental data lies within the limits of ±10%.